Content of The Heavy Metal Cd in Tilapia Fish from Rawa Taliwang Lake - Khairuddin, Khairuddin; Yamin, M.; Kusmiyati, Kusmiyati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The heavy metal Cadmium (Cd) can accumulate in the fish's body. The aim of this research is: To determine the metal content of Cadmium (Cd) in Tilapia fish (Oreochromis niloticus) originating from Lake Rawa Taliwang. The specific benefit is to protect consumers who consume Tilapia from heavy metal contamination. The research was carried out at Rawa Taliwang Lake, namely in an area that was submerged in water. Two stations were chosen for this research, namely in the eastern and western parts of the lake. Method of data collection was carried out using gill nets. Two fish were taken at each station. Next, the tilapia fish samples are put into a plastic bag and then stored in a sample box. The research samples were then analyzed at the Mataram University analytical laboratory and at the Environmental and forestry services West Nusa Tenggara (DLHK NTB) Environmental Laboratory. The data analysis method was carried out by taking tilapia ikab muscle tissue and then analyzing the heavy metal content in the form of Cadmium (Cd) using an Atomic Absorption Spectrophotometer. Measurement of heavy metals in tilapia fish tissue was carried out by adding concentrated HNO3 and HClO4, heating at a temperature of 60-70ºC for 2-3 hours until the solution was clear. Samples are ready to be measured with AAS using an air-acetylene flame. The conclusion of this research is that the content of the heavy metal Cd in Tilapia fish (Oreochromis niloticus) originating from Lake Rawa Taliwang ranges from 0.19 – 2,18 mg/kg (ppm), exceeds the permitted quality standard, namely 0.3 mg/kg.